Factors Related To The Occurrence Of Hypertension At Telaga Dewa Health Center In Bengkulu City - Wilantara, Anggi; Rohani, Tuti; Saputra, Fery Surahman; Sari, Fikitri Marya; Habibi, Julius (Journal Hygeia Public Health, 2024)
Intoduction: Hypertension or high blood pressure is a chronic condition characterized by increased blood pressure on the walls of the arterial blood vessels. According to Riskesdas data, the prevalence of hypertension in Indonesia is 34.1%. Bengkulu Province ranks 26th nationally with a prevalence of 28.14%, with the highest estimated number of cases in individuals aged ≥15 years at Telaga Dewa Health Center, totaling 3,852 cases. This study aims to identify the risk factors associated with hypertension incidence at Telaga Dewa Health Center, Bengkulu City in 2024. Method: This research is quantitative with a cross- sectional design. The sample size is 58 respondents, using accidental sampling techniques with a questionnaire instrument and data processing using SPSS 20. Result and Discussion: The results showed that the majority experienced hypertension, with 39 respondents (67.2%), most were not obese, with 38 respondents (65.6%), nearly half experienced severe stress, with 26 respondents (44.8%), and nearly half had insufficient knowledge, with 31 respondents (53.4%). There was no significant relationship found in the obesity variable (p-value = 0.251 < α 0.05), but there was a significant relationship in the stress variable (p-value = 0.006 < α 0.05) and knowledge (p-value = 0.025 < α 0.05). Conclusion: In this study it can be concluded that there is a significant relationship between stress levels and the incidence of hypertension and there is a significant relationship between the level of knowledge and the incidence of hypertension.